The Role of Government Institutions in Supporting Smallholder Farmers’ Adaptation to Climate Change in Gombe State, Nigeria - Abdullahi, Abdulrashid; E.D, Oruonye; Osigwe, Menwo Ukechi; Danladi, Tukura Ejati (International Journal of Psychosocial Rehabilitation, 2020)
Climate change has now been realized to be an everyday reality, with far reaching consequences, especially for poor agricultural communities, who suffer the most diverse effects of climate change. Over the past few years, efforts have been diverted from reaction, to pre-emptive, in a bid to ensure that the most vulnerable can adapt to the challenges of climate change. As pointed out, most impacts of climate change are felt by poor communities who depends on subsistence agriculture for survival, and therefore in order for them to adapt to climate change, there is need for them to be supported in various ways, by both government and non-government entities. This study aimed to investigate the role played by government institutions in supporting climate change adaptation among smallholder farmers in Gombe State, Nigeria. The primary data used in this study was generated through using structured questionnaire. This was administered to 240 randomly selected members of the farming communities, local leaders, as well as members of government institutions working on environmental management in the State. Data was analyzed using both descriptive and factor analysis methods. Results show that a number of factors are responsible for determining the government support towards adaptation in both crop and animal production among smallholder farmers. The findings also show that government support towards adaptation was provided through different ways, for both crop and animal production. The study findings also revealed different challenges encountered by crop farmers, livestock farmers and government institutions in trying to implement mechanisms of adaptation to climate change in Gombe State, Nigeria. The study recommended that government should engage rural smallholder farmers, non-governmental organizations and civil society in this effort, and that it should encourage local mechanisms in order to ensure sustainability of the adaptation efforts.